SIMULASI KINERJA FORWARD ERROR CONTROL CODING UNTUK SATELIT MIKRO PENGINDERAAN JARAK JAUH - Dwiyanto; Sugihartono (Indonesian Journal of Aerospace, 2011)
Micro satellite application for remote sensing in this time has been expanded and particularly supported by growth of electronics component that low power and small size. Large amount of image data, less of contact time and limited satellite’s power obliges of efficiency mechanism design to assured data satellite communication is accepted properly by earth station. Various of scenario of data transmissions on micro satellite have been developed in order to ensure all data that taken by payload can be delivered and accepted by station earth truly. Forward Error Control Coding or Forward Error Correction method is mechanism that added redundancy bit to delivery data with a purpose to improve error correction of received data. FEC performance can be known by compare of different value of Eb/N0 needed for Bit Error Rate (BER) in common without FEC. In this research conducted simulation performance FEC Reed Solomon by undertaking change of beet amount per symbol, code length and code ability in repairing symbol error. Simulation Result shows getting smaller code rate that used then ever greater code reinforcement. The simulation using forward error control coding Reed Solomon for data transmission remote sensing results code RS(255,223) have best performance with coderate 0,874 and coding gain 3,4dB on value of BER 10-4.